KRISIS LINGKUNGAN BALI DAN PELUANG EKOWISATA - Arida, Sukma (INPUT Jurnal Ekonomi dan Sosial, 2012)
he exploitation of nature resources of Bali have brought the impact for Bali environment as a whole. The negative impact of tourism development in Bali which tend to mass, such as; degradation environment, decreasing the public space of coast, and decreasing the quality and water supply in Bali. This article is try to identify the nature resources problem and ecotourim as the alternative tourism development in Bali.
Keywords: Nature resources, tourism development, ecotourism